The Evaluation of Sociodemographic and Clinical Features of Children and Adolescents Sent for the Examination with the Claim of Committing Crime - Akyüz, Gamze; Beyaztaş, Fatma Yücel; Kuğu, Nesim; Analan, Enver; Doğan, Orhan (The Bulletin of Legal Medicine, 2000)
In this study, it was aimed to determine the socio-demo- graphic features and some clinical factors in connection with the claim of committing crime of the children being 11- 15 years old, sent for the evaluation of criminal responsibility, and to review the similar studies in literature. The socio-demographic features of 33 cases sent to the Departments of Forensic Medicine and Psychiatry, Cumhuriyet University, Medical School, between 01.05.1999-01.12.1999 for the evaluation of criminal responsibility are examined. "Socio-demographic Information Inquiry", "Depression Scale for Children" and "Childhood Abuse and Neglect Inquiry" prepared for the children were evaluated. DSM-IV diagnostic criteria was used for conduct disorder and substance abuse. 93-4 % of the cases were male. The crime- committed areas were Zara and Kangal with a 30.3 % for each and followed by Divriği with a 27.3 %. Of the types of crime, 42.6 % was robbery. Of the cases, 48.5 % had committed crime intentionally and 45.5 % had committed crime collectively. The types of childhood abuse were emotional abuse with 60.6 %, physical abuse with 45.5 % and neglect 36.1 %. The percentage of depression was 27.3 and conduct disorder was found to be 3. In conclusion, the highness of rates of depression and childhood abuse is considered such as the depression and the childhood abuse are rise factors for juvenil delinquency. Key Words: : Juvenile delinquency, penal responsibility, depression, conduct disorder, childhood abuse, neglect